Use of a structured panel process to define antimicrobial prescribing appropriateness in critical care. (26th September 2017) - Dresser, Linda D; Bell, Chaim M; Steinberg, Marilyn; Ferguson, Niall D; Lapinsky, Stephen; Lazar, Neil; Murphy, Patricia; Singh, Jeffrey M; Morris, Andrew M
Abstract: Background: Antimicrobial prescribing is frequently reported as appropriate or inappropriate, particularly in the ICU. However, the definitions used are non-standardized and lack validity and reliability. Objectives: To develop standardized definitions of appropriateness for antimicrobial prescribing in the critical care setting. Methods: We used consensus-based modified Delphi and RAND appropriateness methodology to develop criteria to define appropriateness of antimicrobial prescribing. A multiphased approach with an online questionnaire followed by a facilitated in-person meeting was utilized and included clinicians from a variety of practice areas (e.g. surgeons, infectious diseases specialists, intensivists, transplant specialists and pharmacists). Results: There were a total of 23 criteria agreed upon to define the following categories of antimicrobial prescribing: appropriate; effective but unnecessary; inappropriate; and under-treatment. Conclusions: These standardized criteria for appropriateness may be generalizable to other patient populations and utilized with other tools to adjudicate prescribing practices.